2013
DOI: 10.15376/biores.8.4.5475-5484
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moisture Content on the Mechanical Properties of Moso Bamboo at the Macroscopic and Cellular Levels

Abstract: To better understand how moisture content (MC) affects the longitudinal compressive mechanical properties of bamboo, mechanical tests on both the macroscopic and cellular levels were performed on Moso bamboo (Phyllostachys pubescens Mazei ex H. de Lebaie) at different MCs. At the macroscopic level, the compressive modulus of elasticity (CMOE) was determined using a common mechanical tester, while the indentation modulus of elasticity (EIT) and the hardness (HIT) of the bamboo fiber cell walls were obtained usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…De acuerdo con diversos investigadores (AIS, 2010;Gutiérrez, 2011;Jiang, 2012;Wang, 2013;Xu, et al 2014;Kamiski et al, 2016b), la variación en el contenido de humedad es uno de los factores de mayor afectación en las propiedades mecánicas del bambú. Algunos autores han encontrado que el bambú presenta disminuciones de resistencia de hasta un 30 % cuando se alcanza el PSF (Jiang et al, 2012;Xu, et al 2014).…”
Section: Introductionunclassified
“…De acuerdo con diversos investigadores (AIS, 2010;Gutiérrez, 2011;Jiang, 2012;Wang, 2013;Xu, et al 2014;Kamiski et al, 2016b), la variación en el contenido de humedad es uno de los factores de mayor afectación en las propiedades mecánicas del bambú. Algunos autores han encontrado que el bambú presenta disminuciones de resistencia de hasta un 30 % cuando se alcanza el PSF (Jiang et al, 2012;Xu, et al 2014).…”
Section: Introductionunclassified
“…On the other hand, water sorption rate is also directly related to the ability to treat bamboo, e.g., mold resistant treatment using borate solution, both in terms of the treatment time and uniformity 33 . In addition, the water sorption responses at different structure levels will have an impact on the multiscale mechanical properties of bamboo 34 37 , through the effect of moisture content or EMC 38 , 39 and dynamic moisture diffusivity.…”
Section: Resultsmentioning
confidence: 99%
“…The moisture content of the dry bamboo was determined to be 4.47 ± 0.05% using a method described previously (Onche et al, 2020). Wang et al (Wang et al, 2013) have shown that, for a relative humidity of 15.22%, the corresponding moisture content for the Moso bamboo used in their work was 4.30%, while for 27.19% relative humidity, the corresponding moisture content was 6.04%. Hence, the relative humidity of 18% and corresponding moisture content of 4.52% obtained for the Bambusa Vulgaris-Schrad bamboo that was used in this work are within the range of values reported in an earlier study (Wang et al, 2013).…”
Section: Materials Characterizationmentioning
confidence: 93%